2021
DOI: 10.3390/cimb43030103
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bitter Taste Receptor T2R38 Polymorphisms, Oral Microbiota, and Rheumatoid Arthritis

Abstract: The association of taste genetics and the oral microbiome in autoimmune diseases such as rheumatoid arthritis (RA) has not been reported. We explored a novel oral mucosal innate immune pathway involving the bitter taste G protein-coupled receptor T2R38. This case–control study aimed to evaluate whether T2R38 polymorphisms associate with the buccal microbial composition in RA. Genomic DNA was obtained from buccal swabs of 35 RA patients and 64 non-RA controls. TAS2R38 genotypes were determined by Sanger sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Although 68% studies (17/25) ( Table 1 ) took the dental status into consideration, the method of dental assessment was different across studies. Two studies used the self-reported symptoms for assessment (Tong et al, 2019 ; de Jesus et al, 2021 ). Nine studies provided a full periodontal examination to assess the parameters including probing depth (PD), clinical attachment level (CAL), and bleeding on probing (BOP).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 68% studies (17/25) ( Table 1 ) took the dental status into consideration, the method of dental assessment was different across studies. Two studies used the self-reported symptoms for assessment (Tong et al, 2019 ; de Jesus et al, 2021 ). Nine studies provided a full periodontal examination to assess the parameters including probing depth (PD), clinical attachment level (CAL), and bleeding on probing (BOP).…”
Section: Resultsmentioning
confidence: 99%
“…For example, by analyzing the subgingival dental plaque of patients with RA, Streptococcus was found with significantly higher relative abundance compared with healthy controls by Cheng et al ( 2021 ), but was identified at a lower level in the other two studies (Corrêa et al, 2019 ; Tong et al, 2019 ). Ten studies presented the results at the species level and demonstrated different specific dysbiosis features associated with RA, of which two studies found a higher level of Rothia mucilaginosa in the patients with RA (Zhang et al, 2015 ; de Jesus et al, 2021 ). Two studies had performed periodontal examination on the participants, and thus were able to identify the alterations of oral microbiome in patients with RA without periodontitis (Lopez-Oliva et al, 2018 ; Cheng et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in the saliva of 100 mixed-dentition children, the level of cariogenic bacteria Streptococcus mutans was higher in the AVI/AVI group (Shetty et al 2014). A very recent study showed evidence that polymorphisms in TAS2R38 may be associated with differences in the microbial composition of the buccal mucosa in rheumatoid arthritis (de Jesus et al 2021). These cohort studies establish a preliminary clinical correlation between dental caries and the functionality of taste receptors.…”
Section: Oral Health and Taste Receptorsmentioning
confidence: 99%
“…Although 68% studies (17/25) (Table 1) took the dental status into consideration, the method of dental assessment was different across studies. Two studies used the self-reported symptoms for assessment (Tong et al, 2019;de Jesus et al, 2021). Nine studies provided a full periodontal examination to assess the parameters including probing depth (PD), clinical attachment level (CAL), and bleeding on probing (BOP).…”
Section: General Population Characteristicsmentioning
confidence: 99%
“…For example, by analyzing the subgingival dental plaque of patients with RA, Streptococcus was found with significantly higher relative abundance compared with healthy controls by Cheng et al ( 2021), but was identified at a lower level in the other two studies (Corrêa et al, 2019;Tong et al, 2019). Ten studies presented the results at the species level and demonstrated different specific dysbiosis features associated with RA, of which two studies found a higher level of Rothia mucilaginosa in the patients with RA (Zhang et al, 2015;de Jesus et al, 2021). Two studies had performed periodontal examination on the participants, and thus were able to identify the alterations of oral microbiome in patients with RA without periodontitis (Lopez-Oliva et al, 2018;Cheng et al, 2021).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%